Interaksi Sosial Pasca Konflik Horisontal (Studi Kasus Pada Komunitas Islam-Kristen di Kecamatan Tobelo Utara Kabupaten Halmahera Utara - Jaffar Jaffar (LPPM IAIN Sorong, 2015)
The research aims to analyze and give a description (1) the community of North Tobelo Subdistrict before a horizontal conflict. (2) The process of the horizontal conflict; (3) The social interaction after the horizontal conflict between Moslem and Christian communities in North Tobelo sub-district. This research was carried out at North Tobelo sub-district, North Halmahera regency. This study was conducted as a case study, and qualitative descriptive research. In this research, the main informants were four persons from Moslem community, four persons from the Christian community, and two supporting informants (the head of North Tobelo sub-district and the head of the communication Forum for Religious communities in North Halmahera regency). The data analysis included a componential analysis conducted by reviewing components about the community description before the conflict, the process of horizontal conflict and social interaction after the conflict. The results were then abstracted according to theoretical vies and analyzed based on the results of the research about both communities (Moslem and Christian) The results reveal that the community of North Tobelo regency before the conflict was a peaceful community. The community members have a high tolerance so that they lived peacefully in the rule of customs. The occurrence of horizontal conflict was caused by economic,politics and religion problems. After the horizontal conflict, there was a change in the social structure and in the patterns of social interaction in both communities (Moslem and Christian).